Using the focal object method for development creativity of school children in digital learning - Filippov M. I. (Pedagogy, Psychology, Society, 2020)
The features of the method of focal objects in the implementation of digital education at school are characterized. The demand for the development of creativity of students is justified, taking into account the trends in the expansion of the information and educational environment, computer resources and tools in modern society. The possibilities of the methodological support of the teacher’s practical classes in technological disciplines in the digital age are disclosed. The results of the experiment on the federal project "Grandchildren Tsiolkovsky" in the national program "Digital Economy" are presented.
Keywords: проектирование; design; интернет-ресурсы; Internet resources; информационно-образовательная среда; digital school education; цифровое школьное образование; метод фокальных объектов; креативность обучающихся; focal object method; students' creativity; educational information environment